The Effect Of Work Discipline, Work Load And Work Environment On Employee Performance Of The Tvri Public Broadcasting Institution, North Sumatra, Medan - Melly Febrianti; Samrin Samrin; Saimara A.M Sebayang (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study examines the determinants of employee performance at LPP TVRI North Sumatra Medan, focusing on work discipline, workload, and the work environment. A total of 67 respondents, determined through proportional stratified random sampling, were selected from a population of 203 employees for this quantitative research. Primary data collected via Likert-scale questionnaires were processed using multiple linear regression analysis in IBM SPSS 26, after fulfilling the requirements of classical assumption tests and instrument testing. Empirical findings demonstrate that, both collectively and individually, work discipline, workload, and environmental factors have a significant impact on staff effectiveness. Work discipline was identified as the most influential variable. This research model exhibits high explanatory power, with an Adjusted R^2 of 0.899, indicating that 89.9% of performance fluctuations can be explained by the independent variables studied. Overall, this study provides strategic implications for management to strengthen human resource policies to foster sustainable productivity levels.